On the Edge of Meaning: the Thingness of Artwork - Sverdiolas, Arūnas (Semiotika, 2021)
Semiotics and philosophy both claim the status of a meta-language, hence enter into a dialogue with one another and each tries to translate the other into its own language. Contemporary analysis of material culture is informed by the so-called linguistic turn, which was performed by structuralism and affected all humanities. Ferdinand de Saussure’s semiology and the semiotics of Algirdas Julien Greimas and his colleagues work in this area by extrapolating the notion of the text to various fields of inquiry. The problematics of archeology, architecture, and other artifacts demand thinking through the issue of the matter. The paper provides proof that, in its attempts to respond to this demand, semiotics either stays within the frame of the idealistic semiotic existence of an indeterminate status or deploys metaphysical rudiments-and-supplements.